PERAN KARTOSOEWIRJO DALAM PEMBENTUKAN NEGARA ISLAM INDONESIA 1947-1962 - Aga Itbah Baihaqi (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2019)
Abstract: The purpose of this research is to find out about Kartosoewirjo's struggle in the formation of the Indonesian Islamic State in 1947-1962 in Malangbon, West Java. There are several problems examined in this paper, namely: 1) How is the biography of S.M. Kartosoewirjo 2) How was the condition of the government of the Republic of Indonesia which triggered the emergence of the Kartosoewirjo resistance movement 3) How was Kartosoewirjo's struggle in the formation of the Islamic State of Indonesia. To study this problem, researchers use historical methods, to find out historical facts about the biography of SM Kartosoewirjo and his struggles in forming the Islamic State of Indonesia. To analyze historical facts using approaches that are often used in historical research, namely historical, normative, and political approaches. This study found: 1) S.M. Kartosoewirjo was born on January 7, 1907. His father, Kartosuwirjo, was an orderly who was appointed as an employee by the Dutch, so that Kartosuwirjo could complete the education that Kartosuwirjo had received at the Dutch government at that time. 2) The struggle of a Kartosoewirjo to establish an Islamic state, by calling for Jihad Fi Sabilillah for its goals. Kartosuwirjo gave confidence and lessons about his understanding in government, a country based on the Koran and Hadith. 3) In a historical record in Indonesia, Kartosoewirjo was a rebel against the government of the republic of Indonesia. Keywords: Kartosoewirjo, thought, Islamic state, Indonesia